2005
DOI: 10.4103/0019-5545.55938
|View full text |Cite
|
Sign up to set email alerts
|

Perception of burden by caregivers of patients with schizophrenia

Abstract: Background:There is a dearth of studies assessing the burden of caregivers of patients with schizophrenia and illness-related variables such as age, sex, duration of illness, domicile, martial status, education, employment and previous hospitalization.Aim:The study was conducted to measure the perception of burden by caregivers of patients with schizophrenia and its correlation with nine factors on the Burden Assessment Schedule (BAS) related to spouse, physical and mental health, external support, caregiver's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…An earlier study from India also notes that the sex of the patient did not have a significant correlation with any of the dimensions of caregiver burden (Srivastava, 2005). This is also reported by Sreeja et al ( 2008) who found no significant difference in total burden score between male and female caregivers of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…An earlier study from India also notes that the sex of the patient did not have a significant correlation with any of the dimensions of caregiver burden (Srivastava, 2005). This is also reported by Sreeja et al ( 2008) who found no significant difference in total burden score between male and female caregivers of patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 54%
“…However Srivastava ( 2005) found that duration of illness of ≤6 months was found to have no correlation with any of the sub-dimensions of caregiver burden.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Subjective aspects of burden have been examined far less often, though certain studies have found pattern of high objective and low subjective burden reflecting the caregivers' tolerance and acceptance of the patients' problems (Chakrabarti et al 1995;Kiran 2004;Nehra et al 2005;Roychaudhuri et al 1995). In terms of correlation between high burden and age of the patients, the findings have been inconsistent with some studies reporting high burden to be associated with older age of the patient (Rammohan et al 2002), whereas others report high burden when the patient is young (Srivastava 2005). Higher burden is associated with patient being male (Roychaudhuri et al 1995), less educated (Rammohan et al 2002) and unemployed (Roychaudhuri et al 1995).…”
Section: Caregivers' Issuesmentioning
confidence: 92%
“…Most of the studies have been conducted among patients and caregivers attending hospitals. Majority of the studies have included patients with chronic illnesses (Rammohan et al 2002;Agarwal and Chandhok 2007;Ali and Bhatti 1988;Chadda et al 2007;Chakrabarti and Gill 2002;Chakrabarti and Kulhara 1999;Chakrabarti et al 1995;Chandrasekaran et al 2002;Creado et al 2006;Gautam and Nijhawan 1984;Giel et al 1983;Gururaj et al 2008;Jayakumar et al 2002;Kalra et al 2009;Kataria et al 2002;Kiran 2004;Kumar and Mohanty 2007;Kumari et al 2009;Moily et al 1997;Nehra et al 2005Nehra et al , 2006Nirmala et al 2011;Pai and Kapur 1982;Raj et al 1991;Ranga Rao 1988;Rao et al 1988;Roychaudhuri et al 1995;Saldanha et al 2002;Sekaran et al 2001;Sreeja et al 2009;Srivastava 2005;Thomas 2004;Vohra et al 2000). In general, studies have reported high levels of burden perceived by the caregivers of patients with schizophrenia (Agarwal and Chandhok 2007;Ali and Bhatti 1988;Chadda et al 2007;Chakrabarti and Gill 2002;Chakrabarti and Kulhara 1999;Chakrabarti et al 1995;<...>…”
Section: Caregivers' Issuesmentioning
confidence: 99%